2010
DOI: 10.4028/www.scientific.net/amr.132.220
|View full text |Cite
|
Sign up to set email alerts
|

Basic Ion Exchange Resins as Heterogeneous Catalysts for Biodiesel Synthesis

Abstract: Basic and acidic ion exchange resins were used as catalysts for the synthesis of biodiesel from soybean oil and methanol. The impact of reaction parameters like molar methanol/oil relationship, catalyst mass and reaction temperature were studied. The catalysts did not show deactivation and the reaction medium remained neutral. The performance of the resins was compared against reference catalysts (NaOH; MgO). A strongly basic macroporous resin was the most active catalyst and it was possible to reach 100 % sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Studies on heterogeneous catalysis of biodiesel production reactions have shown that anion (OH -) exchange resins [7][8][9] and cation (-SO3H) exchange resins [10][11][12] are promising catalysts. Catalysis of batch transesterification of triolein with ethanol at 20:1 molar ratio and 50˚C using 4g of OHion exchange resins (PA306) was used to achieve over 98% yield of fatty acid ethyl esters after 5h reaction time without catalyst deactivation [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on heterogeneous catalysis of biodiesel production reactions have shown that anion (OH -) exchange resins [7][8][9] and cation (-SO3H) exchange resins [10][11][12] are promising catalysts. Catalysis of batch transesterification of triolein with ethanol at 20:1 molar ratio and 50˚C using 4g of OHion exchange resins (PA306) was used to achieve over 98% yield of fatty acid ethyl esters after 5h reaction time without catalyst deactivation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Another study also showed that 70% FAME yield was achieved after 0.18h residence time for continuous methanolysis of coconut oil with OHanion exchange resin at 6:1 methanol to oil molar ratio and 60˚C, without catalyst deactivation after 10 cycles [8]. No catalyst deactivation was reported for transesterification of soybean oil with methanol with 3g of OHanion exchange resin (BRI), where reactions at 150:1 methanol to soybean oil molar ratio and 80˚C was used to achieve 97.3% FAME yield after 4h reaction time [9]. One of the cation-exchange resins that have been reported for catalysis of triglyceride transesterification is PTSA -SO3H.…”
Section: Introductionmentioning
confidence: 99%